Global Teleconnections of Rapid Ionospheric Fluctuations as Observed via GNSS Measurements - Enric Monte-Moreno; Manuel Hernandez-Pajares; Heng Yang (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
The rapid fluctuations in the electron content of the ionosphere can significantly affect the performance and reliability of communication and GNSS systems. These fluctuations are closely linked to space weather and can result in simultaneous changes in the total electron content of the ionosphere across multiple regions globally. We show the existence of statistically significant synchronous connections between geographical locations when observing fluctuations in electron content. The two findings concerning rapid fluctuations in the electron content of the ionosphere are: 1) evidence of synchronous teleconnections in rapid local electron content variations across a wide range of geographical regions of the globe; and 2) the influence of the solar cycle on the geographic distribution of teleconnections is relatively minor, primarily impacting the frequency of teleconnections per unit of time. We characterize teleconnection patterns for different space weather variables throughout the 2016–2022 study period, encompassing the descending and ascending phases of solar cycles 24 and 25. Previous research has mainly focused on the impact of ionospheric irregularities in limited regions, weather conditions, and short time periods, while our findings indicate the occurrence of this phenomenon globally and during both high and low space weather activity.